Urinary Angiotensinogen and Renin Excretion are Associated with Chronic Kidney Disease - Annett Juretzko; Antje Steinbach; Anke Hannemann; Karlhans Endlich; Nicole Endlich; Nele Friedrich; Uwe Lendeckel; Sylvia Stracke; Rainer Rettig (Karger Publishers, 2017)
Background/Aims: Several studies sought to identify new biomarkers for chronic kidney disease (CKD). As the renal renin-angiotensin system is activated in CKD, urinary angiotensinogen or renin excretion may be suitable candidates. We tested whether urinary angiotensinogen or renin excretion is elevated in CKD and whether these parameters are associated with estimated glomerular filtration rate (eGFR). We further tested whether urinary angiotensinogen or renin excretion may convey additional information beyond that provided by albuminuria. Methods: We measured urinary and plasma angiotensinogen, renin, albumin and creatinine in 177 CKD patients from the Greifswald Approach to Individualized Medicine project and in 283 healthy controls from the Study of Health in Pomerania. The urinary excretion of specific proteins is given as protein-to-creatinine ratio. Receiver operating characteristic (ROC) curves, spearman correlation coefficients and linear regression models were calculated. Results: Urinary angiotensinogen [2,511 (196-31,909) vs. 18.6 (8.3-44.0) pmol/g, *P<0.01] and renin excretion [0.311 (0.135-1.155) vs. 0.069 (0.045-0.148) pmol/g, *P<0.01] were significantly higher in CKD patients than in healthy controls. The area under the ROC curve was significantly larger when urinary angiotensinogen, renin and albumin excretion were combined than with urinary albumin excretion alone. Urinary angiotensinogen (ß-coefficient -2.405, standard error 0.117, P<0.01) and renin excretion (ß-coefficient -0.793, standard error 0.061, P<0.01) were inversely associated with eGFR. Adjustment for albuminuria, age, sex, systolic blood pressure and body mass index did not significantly affect the results. Conclusion: Urinary angiotensinogen and renin excretion are elevated in CKD patients. Both parameters are negatively associated with eGFR and these associations are independent of urinary albumin excretion. In CKD patients urinary angiotensinogen and renin excretion may convey additional information beyond that provided by albuminuria.